Integration of Problem-Based Learning in Science Learning with Digital Learning to Improve Critical Thinking and Collaboration Skills: A Review - Ainun Mardiyah; Sri Wahyuni; Siti Shofa Assyifaul Qulbi Barid; Sri Rejeki Dwi Astuti (Jurnal Pijar MIPA, 2026)
The integration of digital-based Problem-Based Learning (PBL) is increasingly important to support learning that demands critical thinking and collaboration skills in the technological era. This approach allows the exploration and investigation process to be carried out in a more interactive, flexible, and student-centered manner, making it relevant for improving the quality of 21st-century learning. This study aims to explore the forms of digital PBL implementation and its impact on student competencies through a systematic review. The method used is a Systematic Literature Review (SLR) with article searches in Publish or Perish version 8 and Google Scholar, using the keywords “Problem-Based Learning,” “digital learning,” “critical thinking,” and “collaboration” for the period 2020-2025. The selection process followed PRISMA 2020, resulting in 15 articles meeting the inclusion criteria from the initial 200 articles. Data analysis was conducted using a thematic descriptive approach to identify patterns in findings across three main themes: forms of digital PBL implementation, its effects on critical thinking and collaboration skills, and implementation challenges. The results of the study show that technologies such as Nearpod, Padlet, blended learning, mobile learning, and interactive media play an important role in enriching the PBL stages, while also improving critical thinking and collaboration skills by supporting information access and more dynamic learning interactions. However, implementing digital PBL faces obstacles, including limited facilities, teacher readiness, and variations in students' digital literacy. This study confirms that digital PBL has great potential to improve learning quality, with implications for facilities, teacher training, and the strengthening of digital competencies. Further studies are recommended to develop a more adaptive digital PBL integration model and media innovations that are appropriate for future learning needs.